Reading Digital platform and marginalization from gender perspective - Ms. Nalin Nath (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2026)
Social media has become an indispensable aspect of daily life in contemporary times, enabling people to express opinions and connect with a larger audience. Many social media platforms have created countless opportunities because of their considerable success in generating revenue. Marginalized communities, who have historically struggled to be heard and acknowledged, have found social media a more accessible platform for expressing views and opinions. In recent times however, mainstream media transformed into a limited and rigid space focused on a singular narrative, while social media emerged as a powerful space and tool for marginalized groups.